The Influence of Traditional Games on Students' Emotional Intelligence in Physical Education Learning - Muhammad Fadli (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aims to analyze the effect of the traditional game of hadang on improving students' emotional intelligence in physical education learning at SDN 21 Tangnga-Tangnga. Emotional intelligence is an important aspect in the development of elementary school-aged children that needs to be developed through various learning methods, one of which is through traditional games. This study used a quasi-experimental design method with a pretest-posttest control group design approach. The research subjects consisted of 60 students of grades IV and V who were divided into an experimental group (30 students) who received the traditional game of hadang treatment and a control group (30 students) who followed conventional learning. Data collection used a validated emotional intelligence scale with a reliability of 0.89. The results showed a significant difference between the experimental and control groups with a t-value of 8.742 > t-table 2.002 at a significance level of 0.05. The increase in emotional intelligence in the experimental group reached 32.4% covering aspects of self-awareness, emotional management, motivation, empathy, and social skills. The traditional game of hadang has been proven effect in improving students' emotional intelligence because it involves social interaction, teamwork, emotional control, and decision-making in a competitive yet enjoyable game situation.